2017
DOI: 10.1590/1519-6984.15815
|View full text |Cite
|
Sign up to set email alerts
|

Potential distribution and conservation of the Colobosauroides carvalhoi Soares and Caramaschi, 1998: a rare and endemic lizard of Northeast Brazil

Abstract: Ecological niche modeling has contributed to the investigation of the geographical distribution and conservation of rare or little recorded species. Therefore, we studied the known and potential distributions of Colobosauroides carvalhoi Soares and Caramaschi 1998 and discuss the implications for its conservation. Data were obtained by manual collections made in quarterly samplings in three different regions, considering the regions with occurrence records and surrounding areas. The known distribution was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
1
0
1
Order By: Relevance
“…The entire tribe Ecpleopodini, including Dryadosaura and Colobosauroides (the two genera in close association with Anotosaura based on molecular data), is composed predominantly of forest lizards (Pellegrino et al, 2001;Rodrigues et al, 2005;Rodrigues et al, 2007;Goicoechea et al, 2016), which suggests that the disjoint pattern of distribution observed for A. vanzolinia is the result of past forest retraction and the current presence of the Caatinga Domain (Rodrigues, 2003). Ecological niche modeling of another related species of Ecpleopodini, Colobosauroides carvalhoi Soares & Caramaschi, 1998, obtained very similar results to those of the present study (Magalhães et al, 2017). Using evidence from travertine deposition and megafauna and paleobotanical elements, Auler et al (2004) indicated the presence of semideciduous forest in the past (peak in 900 kyr BP) within what is now dry Caatinga.…”
supporting
confidence: 85%
“…The entire tribe Ecpleopodini, including Dryadosaura and Colobosauroides (the two genera in close association with Anotosaura based on molecular data), is composed predominantly of forest lizards (Pellegrino et al, 2001;Rodrigues et al, 2005;Rodrigues et al, 2007;Goicoechea et al, 2016), which suggests that the disjoint pattern of distribution observed for A. vanzolinia is the result of past forest retraction and the current presence of the Caatinga Domain (Rodrigues, 2003). Ecological niche modeling of another related species of Ecpleopodini, Colobosauroides carvalhoi Soares & Caramaschi, 1998, obtained very similar results to those of the present study (Magalhães et al, 2017). Using evidence from travertine deposition and megafauna and paleobotanical elements, Auler et al (2004) indicated the presence of semideciduous forest in the past (peak in 900 kyr BP) within what is now dry Caatinga.…”
supporting
confidence: 85%
“…Para garantir a sustentabilidade na produção de madeira, é essencial que se tenha um conhecimento detalhado da distribuição geográfica natural da espécie em questão (PINHEIRO et al, 2020), a fim de evitar a exploração em áreas que não são adequadas para o seu crescimento ou que possuam alta sensibilidade ambiental (MAGALHÃES-JÚNIOR et al, 2017). Além disso, é importante obter o conhecimento da ocorrência onde há exploração, para que possa contribuir para a conservação da espécie, pois pode estimular a conservação da vegetação nativa, assim como proporcionar uma renda para as populações locais, o que pode incentivar a manutenção do ecossistema (GIATTI et al, 2021;LIMA et al, 2021).…”
Section: Introductionunclassified
“…where moisture is retained), surrounded by caatinga areas and in a Cerrado-Caatinga transition areas(Soares and Caramaschi 1998;Magalhães-Júnior et al 2017). Diet based mainly on arthropods, being Isoptera, Orthoptera and Blattaria the most representative items(Mesquita et al 2006; Cavalcanti et al in press).…”
mentioning
confidence: 99%